Spirometric Evaluation of Effect of Air Pollution on Pulmonary Functions of Traffic Police in Kathmandu Valley - Yadav, Om Prakash; Pun, Matiram; Mahotra, Narayan Bahadur; S.J.B. Rana, Binaya (Janaki Medical College Journal of Medical Science, 2022)
Background and objectives: Traffic police personnel are exposed to ambient air pollution which leads to important health hazards like impairment of lung functions. The objectives of this study were to measure and compare the pulmonary function parameters of traffic police and general duty police and also aimed to evaluate the effect of job duration on those parameters in Kathmandu valley. Materials and methods: A cross-sectional comparative study was done in a total of 133 healthy, non-smoker, male policemen working in Kathmandu valley for a minimum of one year. Out of them, 70 were from traffic police and 63 were from general duty police. MIR Spirolab II was used for pulmonary function test (PFT) measurement. Statistical analysis was done using SPSS version 20. The results were presented as mean ±SD and Independent sample t-test: was used. The p-value <0.05 was considered statistically significant. Pulmonary functions of the two groups were compared. Results: There was a statistically significant decrease in FEV1, FEV1/FVC and FEF25%=75% among policemen working in Kathmandu valley for seven years or more as compared to those working for less than seven years. Although the traffic police had lower FVC, FEV1, FEV1/FVC and PEF in comparison to the general duty police, these differences were not statistically significant. Conclusion: The findings of this study demonstrated that pulmonary functions of both the traffic and the general duty police decrease with increase in duration of job in Kathmandu valley. The pulmonary functions of the traffic police were lower than their predicted values although they were not significantly lower than those of the general duty police. Keywords: Lung function, Spirometry, Traffic policemen, FVC, FEV1, PEF, FEF25%-75%